2019
DOI: 10.1002/cld.764
|View full text |Cite
|
Sign up to set email alerts
|

Hypotension in Cirrhosis

Abstract: http://aasldpubs.onlinelibrary.wiley.com/hub/journal/10.1002/(ISSN)2046-2484/video/13-6-reading-vora a video presentation of this article Answer questions and earn https://www.wileyhealthlearning.com/Activity/6798610/disclaimerspopup.aspx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…This results in the activation of neurohumoral mechanisms aimed at maintaining adequate tissue perfusion, including beta-adrenergic signaling and the renin-angiotensin-aldosterone system. In patients with portal hypertension, these mechanisms increase cardiac contractility and promote salt and water retention[ 7 ]. When a severe infection ensues, macrovascular[ 8 , 9 ] and microvascular[ 10 ] vasodilatory effects are exaggerated, further decreasing the effective circulating volume and potentiating the neurohumoral response (Figure 1A ).…”
Section: Pathophysiology Of Portal Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in the activation of neurohumoral mechanisms aimed at maintaining adequate tissue perfusion, including beta-adrenergic signaling and the renin-angiotensin-aldosterone system. In patients with portal hypertension, these mechanisms increase cardiac contractility and promote salt and water retention[ 7 ]. When a severe infection ensues, macrovascular[ 8 , 9 ] and microvascular[ 10 ] vasodilatory effects are exaggerated, further decreasing the effective circulating volume and potentiating the neurohumoral response (Figure 1A ).…”
Section: Pathophysiology Of Portal Hypertensionmentioning
confidence: 99%
“…Although patients with cirrhosis were underrepresented in these trials, recent epidemiologic studies suggest parallel improvement in survival among this subset, indicating that management in the ICU is warranted[ 3 - 6 ]. While patients with compensated cirrhosis may respond to the same interventions and may have comparable outcomes to those without cirrhosis[ 7 ], patients with decompensated cirrhosis and clinically significant portal hypertension have marked local and systemic hemodynamic aberrations and hepatic functional impairment that may profoundly impact their management and prognosis. Consequently, the care of these patients should be appropriately tailored based on their unique pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…A baseline hypotension with mean arterial pressure (MAP) of 60–65 mmHg is commonly seen and well tolerated in stable cirrhotic patients through compensatory mechanisms to maintain organ perfusion. Subtle insults, such as propofol sedation, may result in significant hypotension and even circulation compromise 7 . Moreover, increased distribution volume 8 may increase propofol dosage, which may further deteriorate hemodynamic instability during the procedure and delay recovery after the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Subtle insults, such as propofol sedation, may result in significant hypotension and even circulation compromise. 7 Moreover, increased distribution volume 8 may increase propofol dosage, which may further deteriorate hemodynamic instability during the procedure and delay recovery after the procedure. A combination of opioids and propofol for endoscopic procedures can decrease the total dosage of propofol as well as its cardiovascular side-effects, 9,10 but respiratory depression caused by opioids is a major concern for cirrhotic patients, especially for patients with massive ascites.…”
Section: Introductionmentioning
confidence: 99%
“…For example, patients with advanced heart failure or cirrhosis may develop hypotension. Clinical trials have shown that low blood pressure occurs in 10%−15% of patients with heart failure, 11 while hypotension is also a complication of cirrhosis stemming from portal hypertension which results in splanchnic and systemic vasodilation 12 . Therefore, multiple factors may account for the observed association between systolic blood pressure reading ≥140 mmHg and in‐hospital mortality.…”
Section: Discussionmentioning
confidence: 99%